PENILAIAN KINERJA KEUANGAN PERUSAHAAN MELALUI TINGKAT LIKUIDITAS, SOLVABILITAS, AKTIVITAS DAN PROFITABILITAS PADA PERUSAHAAN TELEKOMUNIKASI - Dewi Saptantinah Puji Astuti, Sari Ratih, Rispantyo & (Universitas Slamet Riyadi, 2017)
The study aims to asses the financial performance of companies using financialratio analysis, by taking an object on the telecommunications companies, based onthe development of telecommunications is increasingly with the rapid advance oftechnology and information. Source of data used in the form of secondary data,namely the company’s published financial statements. The type of data used in theform of quantitative and qualitative data. Techniques of data analysis using ratioanalysis and the ratio used is the ratio of liquidity is current ratio, solvency ratio ofdebt to equity ratio, the ratio of activity namely total assets turnover, andprofitability ratio of return on equity. Based on the results of data analysis has beendone, it is known that the performance of the telecommunications company has nothave a good performance. It can be seen from the calculation of the current ratio ofthe telecommunications company can not meet its current liabilities with currentassets, debt to equity telecommunications company has not be said to be goodbecause the amount of liability is greater than the amount of capital available, totalassets turnover telecommunications company has not be said to be good because theamount of assets the company has not been able to produce optimal sales, return onequity telecommunications company has not be said to be good because the netincome earned less than the amount of capital.Keywords: liquidity ratios, activity ratios, solvency ratios, profitability ratios